Colour in the Historical Thesaurus of the Oxford English Dictionary - Kay, C; Alexander, M (2010)
Following 44 years of intensive work at Glasgow University and elsewhere, the Historical Thesaurus of the Oxford English Dictionary (HTOED) was published by OUP in October 2009. Based largely on data from the second edition of the Oxford English Dictionary (OED), supplemented by Old English materials, the project is unique in its historical coverage and in the detailed semantic information captured by its scheme of classification. It will continue to develop in future, both in tandem with, and independent of, the OED. The power of HTOED to illuminate the history of English vocabulary will be demonstrated through an analysis of the semantic field of Colour, which contains about 6000 of the 800,000 or so senses in HTOED. Particular attention will be paid to the subcategory of Red, which predominates throughout the history of English but presents problems if conventional wisdom is followed in separating out Pink as a separate category in the eighteenth century. There will also be discussion of the occurrence of colour words elsewhere in HTOED, and of the cultural implications of objects chosen to typify colours over time.